Avaliação de higienização e manutenção das próteses totais convencionais em idosos de uma instituição de longa permanência - Dutra, Elisa (2021)
The present qualitative cross-sectional study aimed to evaluate the effectiveness of cleaning and maintenance of conventional removable dentures of institutionalized elderly in the São José shelter, belonging to the Lucas Araújo Foundation located in the city of Passo Fundo/RS in January 2019. if the data collection, through the application of a questionnaire by a trained researcher, consisting of a script of 12 questions and subsequent analysis and data tabulation, applied to 18 patients, users of conventional complete removable dentures with an average age of 77 years. Of these, thirteen individuals clean their complete denture 2 to 3 times a day with conventional toothpaste and a toothbrush. All patients analyzed reported having knowledge about the importance of cleaning their complete dentures, but not all of them were able to do it daily. Thus, from the results obtained in this research, it is concluded that, even at advanced ages, patients when motivated, have the ability to learn and clean their removable complete dentures, needing only encouragement and professional guidance.